Implementation of a cell balancing systems for lithium batteries with multi-level monitoring - Wong, Jacky Chew Soon (2024)
As technology advances, the demand for batteries, especially in electric vehicles (EVs), continues to grow. Batteries are frequently combined in series and parallel configurations to reach specific voltage and storage capacity requirements. However, maintaining a balanced state of charge (SoC) across all batteries is crucial for efficient operation during steady state, charging, or discharging. This is typically managed by a battery management system, which monitors various parameters to ensure efficient operation. This project focuses on designing a capacitor-switching active balancer and a monitoring system for lithium iron phosphate batteries, monitoring parameters at different levels, from cell to module to system. The experimental results showed that with the implementation of the cell balancing system, the battery performance is significantly extended by ensuring a balanced SoC across all cells. This led to improved efficiency and longer battery life. The real-time monitoring system provided crucial data on voltage, current, and temperature, enabling optimization of the battery system. This integrated approach demonstrates the system's effectiveness in enhancing lithium iron phosphate battery performance, especially in electric vehicles.